2023
DOI: 10.3390/ijms24032655
|View full text |Cite
|
Sign up to set email alerts
|

Near Infrared Photoimmunotherapy: A Review of Recent Progress and Their Target Molecules for Cancer Therapy

Abstract: Near infrared photoimmunotherapy (NIR-PIT) is a newly developed molecular targeted cancer treatment, which selectively kills cancer cells or immune-regulatory cells and induces therapeutic host immune responses by administrating a cancer targeting moiety conjugated with IRdye700. The local exposure to near-infrared (NIR) light causes a photo-induced ligand release reaction, which causes damage to the target cell, resulting in immunogenic cell death (ICD) with little or no side effect to the surrounding normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 160 publications
0
15
0
Order By: Relevance
“…The combination of CDT and PDT can induce immunogenic cell death (ICD), , ICD is characterized by calreticulin (CRT) expression, adenosine triphosphate (ATP) secretion, and high mobility group protein 1 (HMGB1) release. CRT, ATP, HMGB-1, etc., are collectively referred to as damage-associated molecular patterns .…”
Section: Resultsmentioning
confidence: 99%
“…The combination of CDT and PDT can induce immunogenic cell death (ICD), , ICD is characterized by calreticulin (CRT) expression, adenosine triphosphate (ATP) secretion, and high mobility group protein 1 (HMGB1) release. CRT, ATP, HMGB-1, etc., are collectively referred to as damage-associated molecular patterns .…”
Section: Resultsmentioning
confidence: 99%
“…Interleukin-2 (IL-2) is one of the key factors in the coregulation of cellular and humoral immunities, which can stimulate the proliferation and differentiation of T cells and stimulate the function of other immune cells, and the high expression of IL-2 is an important marker of activated immune activity, , which are tumor cell protectors. In the tumor microenvironment, there are many TAMs preventing proinflammatory attack and anticancer T lymphocyte attack, and the decreased expression of ARG1 indicates that the immunosuppressed M2-type TAMS are converted to antitumor M1-type, and the tumor microenvironment is changed from immunosuppressive to immune type. , Intratumoral tissue immune-related experiments were performed on Balb/c mice-bearing tumor. After 14 days of treatment, an immunofluorescence detection kit was used to analyze the expression of immune-related proteins in tumor tissues of the treatment group and the control group, and the results are shown in Figure , which showed that the levels of internalized CRT in the tumor tissues of all of the treatment groups were increased (the intensity of the green fluorescence was positively correlated with the expression of CRT), in which the αPD-L1 group had the weakest expression, while the CFCFB + αPD-L1 + laser group had the highest expression, from which we can assume that ICD was induced in all treatment groups.…”
Section: Results and Discussionmentioning
confidence: 99%
“…PIT confers distinct advantages over other therapies, such as higher efficacy and fewer side effects owing to the targeted nature of the PIT agents. 113 This innovative approach holds great promise as a potent and highly targeted treatment option for cancer and other diseases. Similar to PDT, PIT can also use NIR OLED as an excitation light source.…”
Section: Application Areas Of Nir Materials and Oledsmentioning
confidence: 99%
“…14a). 113,114 Clinical trials of NIR-PIT for head and neck cancers were initiated in the United States in 2015, with the administration of RM-1929, a conjugate of IR700 and cetuximab, which targets the overexpression of EGFR in HNSCC. The results of the trials indicated that RM-1929 was safe and effective in treating locally recurrent HNSCC that cannot be surgically removed, demonstrated a superior therapeutic effect in athymic nude mouse models compared to cetuximab-based NIR-PIT, which can be attributed to its longer half-life (Fig.…”
Section: Application Areas Of Nir Materials and Oledsmentioning
confidence: 99%